Model predictive control and estimation of managed pressure drilling using a real-time high fidelity flow model. (October 2020) - Park, Junho; Price, Cameron; Pixton, David; Aghito, Manuel; Nybø, Roar; Bjørkevoll, Knut; Hedengren, John D.
Abstract: When drilling an oil or gas well, well pressures may be controlled using a technology called managed pressure drilling. This technology often relies on model predictive control schemes; however, practical limitations have generally led to the use of simplified controller models that do not optimally handle certain perturbations in the physical system. The present work reports on the first implementation of a highly accurate system model that has been adapted for real-time use in a controller. This real-time high-fidelity model approximates the results of offline high-fidelity models without requiring operation by model experts. The effectiveness of the model is demonstrated through simulation studies of controller behavior under various drilling conditions, including an evaluation of the impact of sparse downhole feedback measurements. Highlights: Application of nonlinear MPC for managed pressure drilling. Validation of real-time high fidelity flow model for drilling hydraulics. Real-time parameter estimation using MHE for managed pressure drilling. Control performance comparison of semi- and full-closed loop configurations. Performance validation for three common drilling operations.